1989
DOI: 10.1007/bf00366848
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory therapy in acute endotoxin-induced bovine mastitis

Abstract: Acute mastitis was induced in lactating cows by intramammary challenge with 10 micrograms of Escherichia coli lipopolysaccharide. The cows were monitored clinically prior to and for 96 hours after challenge. Milk production, complete blood counts, serum enzyme activities and milk indicators of inflammation were evaluated. Endotoxin challenge was in 7 groups of 3 cows each. Within the groups, cows were randomly assigned to 3 intravenous treatments: saline controls, steroid (one dose of dexamethasone at 0.44 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
22
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 2 publications
3
22
0
Order By: Relevance
“…These results are similar to those reported in bovine mastitis, after administration of nonsteroidal anti-inflammatory agents (Anderson & Hunt, 1989;Green et al, 1997;Morin et al, 1998). Furthermore, administration of flunixin without antibacterial agents is often practiced.…”
supporting
confidence: 91%
“…These results are similar to those reported in bovine mastitis, after administration of nonsteroidal anti-inflammatory agents (Anderson & Hunt, 1989;Green et al, 1997;Morin et al, 1998). Furthermore, administration of flunixin without antibacterial agents is often practiced.…”
supporting
confidence: 91%
“…These findings are consistent with the antipyretic, anti‐inflammatory and antitoxic properties of flunixin. In cattle, flunixin reduces the plasma concentration of thromboxane B 2 and prostaglandin E 2 and thus, is effective against inflammatory response to endotoxins (Anderson & Hunt, 1989; Espinasse et al ., 1994; Odensvik & Magnusson, 1996).…”
Section: Proportions Of Cows With Complete Uterine Involution and Camentioning
confidence: 99%
“…These ®ndings are consistent with the antipyretic, anti-in¯ammatory and antitoxic properties of¯unixin. In cattle, unixin reduces the plasma concentration of thromboxane B 2 and prostaglandin E 2 and thus, is effective against in¯ammatory response to endotoxins (Anderson & Hunt, 1989;Espinasse et al, 1994;Odensvik & Magnusson, 1996). The process of normal uterine involution is usually completed within 4±5 weeks postpartum and is associated with a massive and sustained release of prostaglandin F 2a (Morrow, 1969;Okano & Tomizuka, 1987;Zain et al, 1995).…”
mentioning
confidence: 99%
“…Pyrexia was not significantly altered by treatment with FM and NDGA. In endotoxin-induced bovine mastitis, FM used at a dose of 1.1 mg/kg has produced variable degrees of antipyresis (ANDERSON et al, 1986;ANDERSON and HUNT, 1989). ANDERSON and HUNT (1989) have suggested that a 2.2mg/kg dose of FM may be more effective in reducing pyrexia in the cow.…”
Section: )mentioning
confidence: 99%
“…The finding of increased levels of eicosanoids in the milk of cows with coliform mastitis has provided a rationale to investigate the therapeutic uses of nonsteroidal antiinflammatory drugs (NSAIDs) in coliform mastitis. A number of studies have examined the use of flunixin meglumine (FM) in experimental coliform mastitis (ANDERSON et al, 1986; LOHUIS et a]., 1989; ANDERSON and HUNT, 1989). FM has antipyretic, antiinflammatory, and analgesic properties, which are thought t o be due, at least in part, to the inhibition of cyclooxygenase by FM (KOPCHA and AHL, 1989).…”
Section: Introductionmentioning
confidence: 99%